Induced Resistance Against Western Flower Thrips by the Pseudomonas syringae-Derived Defense Elicitors in Tomato - Chen, Gang; Escobar-Bravo, Rocío; Kim, Hye Kyong; Leiss, Kirsten A.; Klinkhamer, Peter G. L. (Frontiers in Plant Science, 2018)
Western flower thrips (WFT) Frankliniella occidentalis (Pergande) is a key agricultural pest of cultivated tomatoes. Induced host plant resistance by activating jasmonic acid (JA) signaling pathway constitutes a promising method for WFT control. The phytotoxin coronatine (COR), produced by Pseudomonas syringae pv. tomato DC3000 (Pst), mimics the plant hormone JA-Isoleucine and can promote resistance against herbivorous arthropods. Here we determined the effect of Pst and COR on tomato resistance against WFT, induction of JA- and salicylic acid (SA) associated defenses, and plant chemistry. Additionally, we investigated the presence of other components in Pst-derived and filtered culture medium, and their interactive effect with COR on tomato resistance to WFT. Our results showed that infiltration of COR or Pst reduces WFT feeding damage in tomato plants. COR and Pst induced the expression of JA-associated gene and protein marker. COR also induced expression of a SA-related responsive gene, although at much less magnitude. Activation of JA defenses in COR and Pst infiltrated plants did not affect density of type VI leaf trichomes, which are defenses reported to be induced by JA. An untargeted metabolomic analysis showed that both treatments induced strong changes in infiltrated leaves, but leaf responses to COR or Pst slightly differed. Application of the Pst-derived and filtered culture medium, containing COR but not viable Pst, also increased tomato resistance against WFT confirming that the induction of tomato defenses does not require a living Pst population to be present in the plant. Infiltration of tomato plants with low concentrations of COR in diluted Pst-derived and filtered culture medium reduced WFT feeding damage in a greater magnitude than infiltration with an equivalent amount of pure COR indicating that other elicitors are present in the medium. This was confirmed by the fact that the medium from a COR-mutant of Pst also strongly reduced silver damage. In conclusion, our results indicate that induction of JA defenses by COR, Pst infection, the medium of Pst and the medium of a Pst COR- mutant increased resistance against WFT. This was not mediated by the reinforcement of leaf trichome densities, but rather the induction of chemical defenses.